Vectors of ensuring economic security of energy enterprises in the context of quantum transformation (Economics and region, 2025)
The article emphasises that the key to Ukraine's energy security during the war and post-war years is decentralisation and distributed generation, which inherently involve creating an extensive energy production and transmission system based on multiple sources located near consumers. It is emphasised that distributed power generation has a number of advantages but requires the use of digital technologies, which, with the evolution of digitalisation, are increasingly accompanied by cyber-attacks and cyber incidents. As practice shows, their manifestations seriously affect energy companies' economic security. It is emphasised that with quantum transformation, cyber threats are further exacerbated since quantum computers are quite powerful and instantly destroy the cyphers for access to information and the power system, thus causing large-scale losses to energy enterprises. Repeatability, which requires additional time. It is substantiated that energy companies should already consider a migration plan and take a crypto-agility position that will allow them to quickly update in the event of cyber-attacks. The author considers the chronology of quantum threats and factors that complicate the cybersecurity of energy enterprises. The author points out the abilities of quantum computers compared to classical ones. Examples of technologies designed to mitigate quantum threats to critical infrastructure are given. It is substantiated that measures to prevent quantum threats and minimise the consequences of cyber-attacks and cyber incidents should be taken both at the level of the State and the energy sector, and at the level of territorial communities and energy enterprises. An algorithm for the sequence of actions to create a ‘line of defence’ of electric power enterprises against cyber-attacks and cyber incidents in the context of quantum transformation is proposed. It is substantiated that the introduction of a ‘line of defence’ of electric power enterprises against cyber-attacks and cyber incidents in the context of quantum transformation according to the proposed algorithm will prevent their impact or minimise their consequences and thus guarantee the preservation of economic security of enterprises in the context of growing external threats.
Keywords: economic security of an enterprise; economic losses; severe economic consequences; ‘lines of defence’ of electric power enterprises; cyber defence; cyber hygiene